Chronic pain impairs cognitive flexibility and engages novel learning strategies in rats. Issue 7 (July 2018) - Cowen, Stephen L.; Phelps, Caroline E.; Navratilova, Edita; McKinzie, David L.; Okun, Alec; Husain, Omar; Gleason, Scott D.; Witkin, Jeffrey M.; Porreca, Frank
Abstract : Abstract: Cognitive flexibility, the ability to adapt behavior to changing outcomes, is critical to survival. The prefrontal cortex is a key site of cognitive control, and chronic pain is known to lead to significant morphological changes to this brain region. Nevertheless, the effects of chronic pain on cognitive flexibility and learning remain uncertain. We used an instrumental paradigm to assess adaptive learning in an experimental model of chronic pain induced by tight ligation of the spinal nerves L5/6 (spinal nerve ligation model). Naive, sham-operated, and spinal nerve ligation (SNL) rats were trained to perform fixed-ratio, variable-ratio, and contingency-shift behaviors for food reward. Although all groups learned an initial lever-reward contingency, learning was slower in SNL animals in a subsequent choice task that reversed reinforcement contingencies. Temporal analysis of lever-press responses across sessions indicated no apparent deficits in memory consolidation or retrieval. However, analysis of learning within sessions revealed that the lever presses of SNL animals occurred in bursts, followed by delays. Unexpectedly, the degree of bursting correlated positively with learning. Under a variable-ratio probabilistic task, SNL rats chose a less profitable behavioral strategy compared with naive and sham-operated animals. After extinction of behavior for learned preferences, SNL animals reverted to their initially preferred (ie, less profitable) behavioral choice. Our data suggest that in the face of uncertainty, chronic pain drives a preference for familiar associations, consistent with reduced cognitive flexibility. The observed burst-like responding may represent a novel learning strategy in animals with chronic pain. Abstract : Rats with spinal nerve ligation were impaired relative to controls in flexibly adapting to changing environmental demands.